Theory Consumption of Value: Destination Images in Local Culinary - Aflit Nuryulia Praswati; Wafiatun Mukharomah; Amelia Jihan Ramadhani; Sri Murwanti (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2021)
Purpose: This study aims to analyze the effect of taste value, epistemic value, emotional value on the culinary destination image with tourist attitude as an intervening variable. Research methods: This research uses quantitative methods. Primary data is obtained directly from tourists who have visited and enjoyed local cuisine. The sample was determined using nonprobability sampling with a purposive sampling technique and obtained a sample of 335 respondents. The data collection method in this study used a questionnaire that was distributed online through Google forms. This research was analyzed using SPSS software. Results and discussions: The results of this study indicate that all variables have a significant effect on tourist attitudes. Variable attitude of tourists significantly influence the image of culinary destinations. Taste value, epistemic value, emotional value variables significantly influence the image of local culinary destinations mediated by tourist attitudes. Conclusion: Taste value, epistemic value, and emotional value significantly influence the image of culinary destinations mediated by tourist attitudes.